To study factors influence organizational citizenship behaviors among employees in Majlis Perbandaran Teluk Intan [MPTI] / Nor Shakirah Mohd Shahimi - Mohd Shahimi, Nor Shakirah
In current problem of organization performance, it need to have a workforce of high level in organizational citizenship behavior (OCB). It is refers to discretionary, no required contributions by members to the organizations that employ them. OCB describe an actions in which employees are willing to go above and beyond their prescribed role requirements. The purpose of this study is to examine the relationship between job satisfaction, job motivation, affective organizational commitment and job engagement which are the factors influence in OCB. This study was carried out at Majlis Perbandaran Teluk Intan (MPTI) in Perak. In this study researcher has distributed a set of questionnaire to employees at the all department in MPTI. The number of sample size is 320 respondents. 170 questionnaires were distributed, where only 119 were returned back. Results indicate that positive job satisfaction, job motivation, affective organizational commitment and job engagement are all related to OCB. This research is effective to improve organization which want to create the OCB among employees in organization. The outcome of this study can also be used as a guide to provide an approach for member in organization to implement OCB.